SYNTHESIS OF DIBENZYLBUTANEDIOL LIGNANS AND THEIR ANTI-HIV, ANTI-HSV, ANTI-TUMOR ACTIVITIES - MU XIA,YA (Sociedad Chilena de Química, 2009)
An effcient route to the synthesis of dibenzylbutanediol lignans and their analogues was reported. The syntheses were based on a strategy involving Stobbe condensation and alkylation reaction to give the skeleton of lignan, the resolution of (±)-diacid with quinine, the transformation of functional groups to obtain seven dibenzylbutanediol lignans and one analogue. Among the synthesized lignans, four compounds were natural products. All dibenzylbutanediol lignans and their analogue synthesized were evaluated on HIV Tat transactivation in human epithelial cells, HSV-1 gene and human leukemic, liver, prostate, stomach, and breast cancer cell in vitro, but some compounds displayed weak activity against HIV, HSV and MDA-MB-435 human breast cancer cell.